Ethics and Legal Issues in the Abortion Case - Abdullah, Rizki Aji Rahmawan (Faculty of Law Universitas Negeri Semarang, 2021)
In Indonesia regulated in Law No. 36 of 2009 on health. Any person who deliberately performs an abortion is inconsistent with the provisions referred to in Article 75 paragraph (2) shall be punished with imprisonment of not more than 10 (ten) years and a maximum fine of Rp.1.000.000.000,00 (one billion rupiah). Basically, the treatment of abortion is found in them in life. Some of the driving forces for abortion are quite numerous and the abortion treatment can be viewed in any perspective. One thing that is commonplace among today is such an unwanted pregnancy because of a factor and aims to disrupt the pregnancy by an act of abortion. But the act of abortion is not roughly done deliberately but the existence of an unwanted so that the act of abortion should be done. The notion of abortion of the womb, the fetal exclusion is not appropriate in time whether it is intentional or not.